Estimating the Velocity of Landslide Movement Using Visco-Plastic Model in Jeruk Sub-village, Kulon Progo District, Yogyakarta, Indonesia - Myat Thu Naing; Teuku Faisal Fathani; Wahyu Wilopo (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
A ground movement occurred in March and November 2017 on the hills and paddy fields in Jeruk Sub-village, Kulon Progo District, Yogyakarta Special Province. The landslide movement destroyed two houses in the village and the land is still moving especially in the rainy season. The mitigation of landslide hazard requires understanding of landslide triggering factors and its movement mechanism. This paper applies the slope stability analysis and visco-plastic model to predict the movement mechanism and velocity of a translational landslide. The sliding mass is modeled as a low plasticity silt (homogenous soil). The Limit Equilibrium Method is used to estimate the safety factor, whereas the shear strength parameters on the slip surface were determined by using the back analysis approach. The results of the slope stability analysis showed that the shear strength parameters and the fluctuation of groundwater level strongly influence the stability of the landslide. From visco-plastic model simulation, this slope has slow movement velocity with the range of 11.31 to 175.88 mm/day. It is clarified that the velocity of landslide movement is influenced by soil strength parameters, coefficient of dynamic viscosity, and groundwater level fluctuation.